SPIRITUALITAS KEGEMBALAAN DAN KEPEMIMPINAN DALAM GEREJA - Ohoitimur, Johanis (Pineleng Theological Review, 2024)
Leadership is always an interesting topic to discuss because of its dynamic nature. There is no one single standard leadership concept. Every era and every context requires unique leadership system, pattern, and approach. Leadership in the Church requires the spirit of a good shepherd (pastor bonus). That is the main theme of this article. Wherefore Catholic Church is taken as the context and perspective, the reflection on leadership in this article refers to the official views in Church documents and the belief of the Pope Francis in Rome as the leader of the Church. The research results from Covey and Collins are also presented to show that the demands for basic pastoral and leadership characters in the Church are appropriate and relevant to the spirit of leadership needed today. This research uses a qualitative method that relies on literature study and critical reconstruction of thoughts based on the bibliographic data collected.